The Crime of Genocide: Between Text and Reality In International Law (The Palestinian Reality As A Model) - Hatem, Duaa; Kitan, Esraa (Journal of Legal Sciences, 2026)
Genocide is one of the most serious types of international crimes due to its negative consequences for all of humanity. Its seriousness is evident in that it threatens an entire group or groups for national, ethnic, religious, etc. reasons, Due to the large number of violations and serious practices witnessed in some regions of the world, especially after World War II, they gained the attention of legal and jurisprudential figures, and were subsequently framed at the international level, as the efforts of the international community focused on seeking to find an international legal cover to criminalize and punish acts of genocide, As a result, the Convention on the Prevention and Punishment of the Crime of Genocide was concluded in 1948, and interest in reducing this crime has continued, as this has been emphasized by countries’ efforts to establish an international criminal court competent to try persons who commit international crimes, including genocide, This resulted in the establishment of the International Criminal Court, as well as the establishment of special international criminal courts for this purpose. However, despite the existence of international agreements and international criminal courts, the crime of genocide continues to occur, and the closest realistic case is the genocide being committed by the Zionist entity against the Palestinian people, Indiscriminately targeting civilians and protected objects in clear violation of international law, which prompted South Africa to file a lawsuit before the International Court of Justice on the basis that the basic principles and standards of international law, such as the prohibition of genocide, are obligations towards all (erga omnes) Violation of these obligations is considered a crime against the international order, which gives any state the right to take the necessary measures to ensure that such violations are prevented.